New insight into the electrodeposition of NiCo layered double hydroxide and its capacitive evaluation. (10th March 2020) - Wang, You; Yin, Zhoulan; Yan, Guochun; Wang, Zhixing; Li, Xinhai; Guo, Huajun; Wang, Jiexi
Abstract: Although the peculiarities of electrodeposition in the preparation of metal hydroxides is quite attractive, adequate interpretation of this process still lacks. Here, a novel interpretation of the electrodeposition of nickel cobalt double layered hydroxides (NiCo-LDHs) is proposed. Different from the traditional strategies implemented in the pure nitrate or nitrate-assisted electrolytic baths, the sulfate solution with thiourea (TU) additive is used. Benefited from the chelating and inducing effects of TU, honeycomb-shaped NiCo-LDH nanosheets can be successfully electrodeposited on nickel foam (NF). When performed as free-standing electrodes, these integrated electrodes show a robust capacitive performance. Specifically, NC2S12-15/NF (deposition for 15 min) electrode can deliver remarkable electrochemical properties, such as large capacity (1198 F g −1 at 1 A g −1 ), excellent rate performance (1000 F g −1 at 100 A g −1 ) and good cycling stability. Additionally, the NC2S12-15/NF//activated carbon (AC) hybrid capacitor (HC) can sustain extraordinary cycle life (88.3% retention for 10, 000 cycles) and high energy density (29.1 Wh kg −1 ), further demonstrating the qualified capacitive behavior of NC2S12-15/NF electrode. This work provides a new insight into the electrodeposition of metal LDHs based on the design of the electrolyte solution.